Modeling of polygons of maximum passenger route transport accessibility by the example of the transport system of Ukraine - Dolia, Kostiantyn; Davidich, Yuri; Dolia, Olena; Lyfenko, Sergey; Uhodnikova, Olena (Technology audit and production reserves, 2017)
The state (regional) transport system is analyzed on the example of Ukraine. The road network of railways and highways of Ukraine is considered, which consists of more than 30 thousand arcs and knots. The models of the network studied are constructed using ArcMap geoinformation technologies. This provides a description of the network elements with geographical accuracy. One of the most problematic areas of engineering and in particular transport networks is the determination of their maximum potential performance indicators. Formalization of certain parameters determines the planning of technical indicators of flows in the network. Based on the results of the simulation of polygons of maximum passenger route transport accessibility for various modes of transport, it is determined that the characteristics of the model set of polygons are influenced by both the selected network model and the connection speed. It is proved that at the same speed of movement polygons constructed in different networks differ. This is due to the individual features of the networks, It has been established that within 1.5 hours of driving, a railway track with a speed of 68 km/h does not reach any nodes (cities) in both networks, and an automotive polygon with the same speed contains one node (city). A polygon constructed on railway networks with a ride within the limits of 1.5 to 3 hours contains one transport node, and automobile under these conditions – two. When examining a landfill that meets the transport accessibility by rail networks within the range of 5 to 8 hours, there are eleven transport nodes, and the automotive network in these conditions is thirteen. Comparing rail and road transport networks, it can be argued that the road transport network has a larger service area than the railway. The carried out researches can be used at the decision of questions of planning of time expenses and power resources in the course of transportation.